2021
DOI: 10.1186/s12913-021-07072-1
|View full text |Cite|
|
Sign up to set email alerts
|

Factors contributing to the recruitment and retention of rural pharmacist workforce: a systematic review

Abstract: Background Recruiting and retaining medical, nursing, and allied health professionals in rural and remote areas is a worldwide challenge, compromising continuity of care and population health outcomes in these locations. Specifically, pharmacists play an essential and accessible frontline healthcare role, and are often the first point of contact for health concerns. Despite several incentives, there remains a maldistribution and undersupply of pharmacists in rural and remote areas across many p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 57 publications
1
27
0
Order By: Relevance
“…Previous systematic reviews on recruitment and retention of professionals, such as general practitioners working in rural areas 49 , 50 , 51 , 52 , 53 , 54 ) , have indicated that early exposure to rural practice and/or training can contribute to their recruitment and retention 49 , 51 , 52 , 54 ) . Although the detailed mechanisms remain unclear, such exposure is thought to enhance the affinity for work in rural areas.…”
Section: Discussionmentioning
confidence: 99%
“…Previous systematic reviews on recruitment and retention of professionals, such as general practitioners working in rural areas 49 , 50 , 51 , 52 , 53 , 54 ) , have indicated that early exposure to rural practice and/or training can contribute to their recruitment and retention 49 , 51 , 52 , 54 ) . Although the detailed mechanisms remain unclear, such exposure is thought to enhance the affinity for work in rural areas.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the study also showed that feeling like the doctor or nurse of the town favours retention in rural areas. Establishing a meaningful relationship with patients is valued very highly but not enough to improve retention [10,29,31]. The rural lifestyle is a negative aspect when it is seen as a barrier to retention globally [32], so further research should be carried out on aspects that can help make rural life attractive to young people.…”
Section: Factors Related To the Concept Of Rural Lifementioning
confidence: 99%
“…Researchers, policy-makers and communities in Japan, the USA, Australia and Canada have attempted different strategies to recruit and retain rural workforce professionals. [11][12][13] To recruit health professions in particular, strategies have included financial incentives, offering unique reimbursement schemes, marketing the benefits of rural living, or hiring specialised recruiters. Overall, these strategies have seen relatively poor results, with the greatest success coming from financial incentives.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%